2020
DOI: 10.1002/slct.202003584
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Lamellar‐Structured MnO2@graphene for High Performance Li, Na and K ion Batteries

Abstract: Finding suitable electrode materials for energy storage devices with large ions like Na+ and K+ is notoriously difficult. Herein, MnO2@graphene with hierarchical lamellar structure has be synthesized. The flower‐like lamellar‐structured MnO2 and nanosheets of graphene combine together to form the composite with vast space for large ions to transport and store, as well as huge surface area for reactions. Sandwiched between graphene nanosheets, electrical conductivity and mechanical properties of MnO2 are highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Zhang et al 89 reported three different three-component reactions for the synthesis of 1,5-BZDs (33) containing a indole ring introduced by Fe 3 O 4 @SiO 2 -PTSA as a magnetic nanocatalyst in EtOH. All reactions involved two common components, namely, OPD (1) and isatin (30), but the third component was ethyl acetoacetate (31) or 3-butyne-2-one (32) or benzoylacetone (14) and gave product (33).…”
Section: 5-bzdsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al 89 reported three different three-component reactions for the synthesis of 1,5-BZDs (33) containing a indole ring introduced by Fe 3 O 4 @SiO 2 -PTSA as a magnetic nanocatalyst in EtOH. All reactions involved two common components, namely, OPD (1) and isatin (30), but the third component was ethyl acetoacetate (31) or 3-butyne-2-one (32) or benzoylacetone (14) and gave product (33).…”
Section: 5-bzdsmentioning
confidence: 99%
“…Zhang and colleges 89 developed an efficient method for the synthesis of BZDs (33) using substituted OPD (1), N , N -dimethylformamide dimethylacetal (44), aromatic acetone (10) and isatin (30) in ethanol at reflux to RT. The authors obtained 10 new compounds (33) in 5–12 h in 79–90% yield using various aromatic ketones and substituted OPD.…”
Section: Synthetic Approaches Of Bzdsmentioning
confidence: 99%
“…Sandwiched between graphene nanosheets, the electrical conductivity and mechanical stability of MnO 2 electrodes are highly enhanced, enabling them to withstand large current shocks and longtime cycling. 12 Zhang et al constructed an integrated array (N-CNSs@MnO 2 ) by rationally anchoring the active MnO 2 on a novel N-doped porous carbon nanosheet (N-CNS) array grown on carbon cloth, which had good flexibility, high conductivity, and large porosity. 13 However, neither the one-dimensional carbon nanotubes nor the two-dimensional nanosheets and graphene can effectively provide enough ion diffusion paths and volume expansion space.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al synthesized a hierarchical lamellar-structured MnO 2 @graphene, in which the lamellar-structured MnO 2 and nanosheets of graphene combined together to form the composite with a good electronic conductivity as well as a huge surface area for reactions. Sandwiched between graphene nanosheets, the electrical conductivity and mechanical stability of MnO 2 electrodes are highly enhanced, enabling them to withstand large current shocks and longtime cycling . Zhang et al constructed an integrated array (N-CNSs@MnO 2 ) by rationally anchoring the active MnO 2 on a novel N-doped porous carbon nanosheet (N-CNS) array grown on carbon cloth, which had good flexibility, high conductivity, and large porosity .…”
Section: Introductionmentioning
confidence: 99%
“…Benefitting from the abundant K resources, [1][2][3][4][5] the superior electrical conductivity of Se than that of S (Se: 1 × 10 À 3 S m À 1 ; S: 5 × 10 À 28 S m À 1 ) and high theoretical specific capacity (675 mAh g À 1 ) and volumetric capacity (3253 mAh cm À 3 ) of Se, [6][7] KÀ Se battery has been regarded as one of the most promising candidates for Li-ion batteries. Unfortunately, just like sulfur-based batteries, [8] the Se cathode also suffers from similar obstacles in particle application, such as the enormous volumetric variation of Se (nearly 400 % during cycling), [9] the profound shuttle effect of potassium polyselenides (KPSs) and sluggish reaction kinetics of Se species, [8,[10][11][12] which could lead to rapid capacity decay and lower utilization of active Se.…”
Section: Introductionmentioning
confidence: 99%